Sleep characteristics in child and adolescent offspring of parents with bipolar disorder: a case control study - Sebela, Antonin; Novak, Tomas; Kemlink, David; Goetz, Michal (BMC psychiatry, 2017)
BACKGROUND: Impairment of sleep and circadian rhythm is a typical feature of bipolar disorder (BD). We carried out an exploratory cross-sectional case-control study to extend the knowledge of sleep characteristics in offspring at risk for BD. METHODS: We investigated 42 offspring of bipolar parents (OB) (mean age 12.5 ± 3.2) and 42 sex and age matched comparison offspring of healthy parents. We administered the Pediatric Sleep Questionnaire, the Morningness/Eveningness Questionnaire and The General Behavior Inventory Sleep Subscale (GBISS) to assess circadian preference, and to identify sleep impairment symptoms. In addition, the participants completed 14 days of actigraphy to characterise sleep and wake patterns. The current psychopathology profile was assessed using Kiddie Schedule for Affective Disorders and Schizophrenia. RESULTS: Prevalence of sleep disturbance symptoms was higher among OB than controls (headache after waking up, 17.9% vs. 2.4%, p = 0.03; excessive daytime sleepiness, 38.5% vs. 10.0%, p = 0.004; apparent tiredness at wake-up times, 43.6% vs. 15.0%, p = 0.007 and nightmares, 21.6% vs. 2.4%, p = 0.01), but the differences between groups were not significant after adjusting for current psychopathology. OB had higher GBISS total score (parental version, p < 0.001; self-assessment, p = 0.07) than the controls. OB had higher preference for eveningness than the controls (p = 0.047). According to the actigraphy, OB had longer sleep onset latency (p = 0.048) than the controls. CONCLUSION: Evidence suggests that the offspring of bipolar parents experience sleep disturbance symptoms, which was associated with psychopathology in this study. Prospective longitudinal sleep studies would clarify whether sleep disturbance could be a predictor of mood disorder onset in this high-risk population.
Keywords: Circadian Rhythm; Parents; Cross-Sectional Studies; Sleep Wake Disorders; poruchy spánku a bdění; Male; Self-Assessment; mladiství; cirkadiánní rytmus; bipolární porucha; průzkumy a dotazníky; mužské pohlaví; Offspring; Sleep; studie případů a kontrol; Bipolar disorder; průřezové studie; Adult; aktigrafie; Prospective Studies; sebezhodnocení (psychologie); dítě; Child of Impaired Parents; Bipolar Disorder; Child; High-risk; ženské pohlaví; Humans; prospektivní studie; dítě postižených rodičů; Surveys and Questionnaires; Actigraphy; dospělí; Female; Adolescent; rodiče; lidé; Case-Control Studies